2022
DOI: 10.7573/dic.2021-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes: how to manage overweight and obesity in type 2 diabetes mellitus

Abstract: The prevalence of obesity worldwide continues to increase substantially. Obesity is a chronic disease that can lead to other health conditions, including type 2 diabetes mellitus (T2DM). A variety of treatment options are available to treat T2DM. With its prevalence increasing, it is essential that healthcare professionals assess how their patients’ current diabetes treatment is being managed to avoid further weight gain in those with overweight or obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Our data are related to a study in which aged black garlic extract was used as a supplement in a high-fat diet-fed animal model [32]. Obesity is linked to a high incidence of steatosis, including non-alcoholic fatty liver disease (NAFLD) [33]. Reactive oxygen species are primarily produced in fatty liver disease due to the over-accumulation of hepatic lipids and the oxidation of fatty acids [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are related to a study in which aged black garlic extract was used as a supplement in a high-fat diet-fed animal model [32]. Obesity is linked to a high incidence of steatosis, including non-alcoholic fatty liver disease (NAFLD) [33]. Reactive oxygen species are primarily produced in fatty liver disease due to the over-accumulation of hepatic lipids and the oxidation of fatty acids [34].…”
Section: Discussionmentioning
confidence: 99%
“…The Global Burden of Disease study found obesity to be the main contributor to multimorbidity and years lived with disability [15]. Furthermore, The increasing global prevalence of obesity is thought to be the main driver for the increase in type 2 diabetes mellitus [16]. This has led to increased risk of cardiovascular disease and end organ damage, such as stroke, heart disease and diabetic nephropathy.…”
Section: The Emergence Of Human Multimorbiditymentioning
confidence: 99%
“…Excessive fat accumulation is a major characteristic of obesity, and the latter has become an important global public health problem [3]. Obesity increases the risk of hypertension, dyslipidemia, cardiovascular disease, and type 2 diabetes mellitus [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%